JURISDICTIONAL CONFLICT AND CRIMINALIZATION OF ISLAMIC PHILANTHROPY DISPUTES: RECONSTRUCTION OF THE AUTHORITY OF RELIGIOUS COURTS TO SUPPORT DEVELOPMENT GOALS SUSTAINABLE DEVELOPMENT (SDGs) - A. Wafi (Proceeding International Conference on Social Sciences, 2026)
One way to realize the SDGs in Indonesia is through Islamic philanthropy. However, there is a jurisdictional ambiguity between the civil authority of the Religious Courts and criminal law, which hinders this potential. This is evident in the tendency to criminalize philanthropic management disputes, using articles on fraud or embezzlement, often leading to asset confiscation and the interruption of social benefits. This reality is diametrically opposed to the ethos of the SDGs, including but not limited to SDG 1, which aims to eradicate poverty, and SDG 16, which aims, among other things, to create peace, justice, and strengthen law enforcement through stronger institutions. This research is a case study of a structural jurisdictional conflict between civil religious law and criminal law. Although Law Number 3 of 2006 on Religious Courts explicitly authorizes Islamic Philanthropy disputes to be resolved, law enforcement has practically transferred these cases to the General Courts through articles of the Criminal Code. This has created a systematic implementation vacuum and marginalized the constitutional competence of the Religious Courts, and is contrary to the principle of ultimum remedium. This jurisdictional conflict research uses a normative juridical method with a statutory, case, conceptual, and historical approach and is enriched by the theory of the rule of law, judicial power, Islamic personality, and progressive law. The novelty of this research is the model of authority reconstruction through a pre-judicial review mechanism, which "establishes the Religious Court as the 'constitutional guardian' of philanthropic assets in Indonesia." This model is oriented to establish the Religious Court as an institution authorized to conduct initial examinations of criminal reports of ZISWAF through the authority of religious civil law. This approach ensures legal certainty and demonstrates the effective function of Islamic philanthropy as a key pillar in sustainable development.